Pendekatan Etnopedagogik Dalam Pendidikan Agama Islam (Tinjauan Ilmu Pendidikan Islam) - Maria, Anly; Kurniawan, M Parhan (STAI Al-Musaddadiyah Garut, 2024)
Culture is a multifaceted concept that encompasses how people live, think, feel, believe, and seek what aligns with their cultural norms. Cultural phenomena represent the human way of life, shaped by human creativity, emotion, and the divine will. The interplay between religion and culture is profound, leading to the emergence of ethnopedagogy. Ethnopedagogy is an educational praxis rooted in local wisdom, encompassing various domains. It views local wisdom as a source of innovation and skills that can be harnessed for societal benefit. This study aims to describe the Ethnopedagogical Approach in Islamic Religious Education. The research adopts a library-based approach (Library Research), involving an examination of written sources on Ethnopedagogy and Islamic Religious Education as discussed by experts. The qualitative research method is employed, focusing on content analysis of Ethnopedagogy and relevant textual materials. The findings indicate that the Ethnopedagogical approach in Islamic Religious Education emphasizes an educational model that consistently integrates local cultural values and religious principles, considering both cultural and religious aspects on a global scale. Through this approach, ethnopedagogy is expected to find its essence in achieving the goals of education. Keywords : Ethnopedagogical Approach; Islamic Religious Education; Islamic Education Studies